Biblical studies on the Internet a resource guide - Worth, Roland H., 1943- (McFarland, 2008)
"The new edition includes more than 4,800 resources available at more than 10,000 Internet sites that provide information on a range of biblical study topics including Bible translations in English and other languages, audio translations, commentaries, dictionaries, and other resource materials including ones in Greek, Hebrew and other ancient languages"--Provided by publisher.